2010
DOI: 10.3348/jksr.2010.62.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT Assessment of Lymph Node Size for Nodal Staging in Patients with Potentially Operable Squamous Esophageal Cancer and the18F-FDG Positron Emission Tomography CT Correlation

Abstract: Purpose:To investigate the size criteria of multidetector computed tomography (MD-CT) for the evaluation metastatic lymph nodes (LNs) for potentially operable squamous esophageal cancer, and to compare this information with the results of positron emission tomography-CT (PET-CT). Materials and Methods: Twenty-four patients who underwent radical esophagectomy for esophageal cancer were studied. All patients had preoperative MDCT and PET-CT. The MDCT findings were compared with those of PET-CT and were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…This present study detailed the assessment of pathological LN metastasis using preoperative FDG‐PET LN status in patients with ESCC who underwent surgery post‐NCT and determined the association between preoperative FDG‐PET LN status and prognosis. LN status assessed using FDG‐PET significantly correlates with pathological LN metastasis in patients with esophageal cancer treated with surgery alone, neoadjuvant chemoradiotherapy (NCRT), and NCT 16–18,23–31 . A case‐by‐case analysis revealed that the sensitivity, specificity, and accuracy of FDG‐PET for LN status pre‐ and post‐NCT were 42.7%–45.9%, 90.3%–92.1%, and 62.6% , 16,18 similar to our results.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This present study detailed the assessment of pathological LN metastasis using preoperative FDG‐PET LN status in patients with ESCC who underwent surgery post‐NCT and determined the association between preoperative FDG‐PET LN status and prognosis. LN status assessed using FDG‐PET significantly correlates with pathological LN metastasis in patients with esophageal cancer treated with surgery alone, neoadjuvant chemoradiotherapy (NCRT), and NCT 16–18,23–31 . A case‐by‐case analysis revealed that the sensitivity, specificity, and accuracy of FDG‐PET for LN status pre‐ and post‐NCT were 42.7%–45.9%, 90.3%–92.1%, and 62.6% , 16,18 similar to our results.…”
Section: Discussionsupporting
confidence: 86%
“…LN status assessed using FDG-PET significantly correlates with pathological LN metastasis in patients with esophageal cancer treated with surgery alone, neoadjuvant chemoradiotherapy (NCRT), and NCT . [16][17][18][23][24][25][26][27][28][29][30][31] A case-by-case analysis revealed that the sensitivity, specificity, and accuracy of FDG-PET for LN status pre-and post-NCT were 42.7%-45.9%, 90.3%-92.1%, and 62.6% , 16,18 similar to our results.…”
Section: Rfs and Os Versus All Ln Findings Pre-and Post-nct Using Fdg...supporting
confidence: 89%
See 2 more Smart Citations